"Jean-Pierre, c'est moi": polyglossia and blurred identities in the films of Jacques Audiard. Issue 1 (April 2018) - Massonnat, François
Abstract : This article engages a heretofore unexplored dimension of Jacques Audiard's work, the prevalence of languages other than the director's native French. Winner of the Cannes Festival Palme d'Or, Dheepan (2015), whose dialogues are predominantly in Tamil, constitutes the most extreme manifestation of polyglossia in the director's filmography. Each of his earlier films participates in a system of representation in which communication never comes easily, and in which characters' success is predicated upon their mastery of the French language. They show a France defined by the brutality of human relationships and incommunicability between people, which only language transcends. Communication proves all the more difficult because nobody's identity is to be taken for granted. Indeed, far from cinematic clichés picturing France as a homogenous, museum-like place, Audiard strives to represent a multilingual, multicultural, and postnational society. Finally, the confrontation of multiple languages within his films allows Audiard to self-define as a global auteur whose cinema seeks to reach beyond a strictly national audience and to address an international market.